Arabic Language Learning Evaluation in Higher Education with Context Input Process Product (CIPP) Model - R.A. Umi Saktie Halimah; Ibnu Hadjar (Arabic Education Program IAIN Pekalongan, 2018)
Evaluation of Arabic language learning in higher education is needed for quality assurance of a learning system. The evaluation should not assess the mere students’ learning output, but involve all aspects of learning program including objectives, planning, implementation and output. This study aims to uncover the implementation of evaluation of Arabic learning program in higher education with the CIPP model, from the emergence of the idea to the result achieved after the program is implemented. It is a theoretical study, which is not based on empirical data in the field. The application of the CIPP model in evaluating Arabic language learning in higher education is conducted by collecting data and information about context, input, process and products of a learning program comprehensively and continuously. More specifically, context evaluation is directed to assess data concerning the purpose and background of a learning program. Input evaluation is conducted to examine the accuracy of the curriculum, students, lecturers and infrastructures. Meanwhile, process evaluation is carried out to reveal the suitability of the curriculum, teaching materials and media in a learning activity. Product evaluation is intended to provide data and information about the outputs and outcomes of Arabic language learning.